PENGARUH LITERASI KEUANGAN TERHADAP PROFITABILITAS USAHA MIKRO KECIL DAN MENENGAH DI KOTA TANGERANG - Endarto, Eko Agus Prasetyo; Tirtana, Aloysius Alfando (Ultimaccounting Jurnal Ilmu Akuntansi, 2020)
Financial literacy is important to improve personal and business financial management skill, especially for small and medium enterprises. Several previous studies have shown an influence between financial literacy and their profits. This research wants to examine whether there is an influence between financial literacy which consists of financial knowledge, behavior and attitude towards SME profits in Tangerang City. Structural Equation Modelling is used as a statistical tool to prove the specified hypothesis. By processing the data, it was found that there was a positive influence between financial literacy and profit. Keywords: Financial Literacy, Financial Knowledge, Financial Behavior, Financial Attitude, Small Medium Enteprise